Additives to Coal-Based Fuel Pellets for the Intensification of Combustion and Reduction in Anthropogenic Gas Emissions; Applied Sciences; Vol. 10, iss. 19 - Klepikov M. V. Dmitry Mikhaylovich; Kudelova T. Tereza; Paushkina K. K. Kristina Konstantinovna; Strizhak P. A. Pavel Alexandrovich (2020, 2020)
Title screen